Predicting the spectral effects of soils on high concentrating photovoltaic systems. (February 2015) - Burton, Patrick D.; King, Bruce H.; Riley, Daniel
Graphical abstract: Highlights: Soiling losses on HCPV systems may be influenced by the spectral properties of soil. Triple junction cell responses to changes in incident spectrum were modeled. Artificial soils deposited on glass slides were used to supply the transmission data. The current balance was sensitive to spectral variations due to mineral pigments. Abstract: Soiling losses on high concentrating photovoltaic (HCPV) systems may be influenced by the spectral properties of accumulated soil. We have predicted the response of an isotype cell to changes in spectral content and reduction in transmission due to soiling using measured UV/vis transmittance through soil films. Artificial soil test blends deposited on glass coupons were used to supply the transmission data, which was then used to calculate the effect on model spectra. The wavelength transparency of the test soil was varied by incorporating red and yellow mineral pigments into graded sand. The more spectrally responsive (yellow) soils were predicted to alter the current balance between the top and middle subcells throughout a range of air masses corresponding to daily and seasonal variation.